Pengembangan Media Pembelajaran Pop-Up Book Digital dengan Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas IV SD - Anis Sa'adah; Sri Sami Asih (Jurnal Penelitian Pendidikan IPA, 2025)
The results of the pre-research conducted by researchers at SD Negeri Jontro show that there are two main problems, namely the limitations of learning media and low student learning outcomes, especially in the science and science subject grade IV. This study aims to develop, evaluate, and test the effectiveness of digital pop-up book media with the Contextual Teaching and Learning (CTL) approach, with a focus on improving the learning outcomes of grade IV elementary school students. The method applied in this study is Research and Development (R&D), which is modified into eight stages, namely potential and problem identification, data collection, product design, design validation, design revision, product trial, product revision, and application trial. The results of the assessment from media experts showed a percentage of 86% and material experts showed a percentage of 90%, which is classified as very feasible. In addition, the response from the classroom teacher reached 92.85% and the student response was 94%, both of which were also considered very feasible. The media effectiveness test carried out by T test analysis showed a significance value of 0.000. In addition, the N-Gain calculation yields a value of 0.84 which is included in the high category. Thus, digital pop-up book media with the Contextual Teaching and Learning (CTL) approach can be considered very feasible and effective to improve the learning outcomes of social studies students in grade IV.